Pengaruh Organizational Justice Terhadap Kinerja Karyawan CV. KUDA LAUT MAS Lumajang Jawa Timur - Jonatan, Stephanus; Wardoyo, Dewie Tri Wijayati (Jurnal Ilmu Manajemen, 2022)
This research is motivated by the phenomenon at CV. XXX, which shows that distributive justice, procedural justice and interactional justice are not yet optimal in the company, discusses employee performance at CV. XXX and analyzing the influence of Organizational Justice. The object of this research is employee of CV. XXX and the data collection technique in this research is using saturated samples. The total number of respondents in this study was 51 people who distributed questionnaires directly. This research is included in the type of quantitative research using data analysis methods in the form of multiple linear regression on SPSS software. The hypothesis testing technique uses the t test. The research results obtained are that Distributive Justice has a positive and insignificant effect on employee performance, Procedural Justice has a significant positive effect on employee performance, Interactional Justice has a significant positive effect on employee performance.